“Omics” Technologies for the Study of Soil Carbon Stabilization: A Review - Overy, David P.; Bell, Madison A.; Habtewold, Jemaneh; Helgason, Bobbi L.; Gregorich, Edward G. (Frontiers in Environmental Science, 2021)
Evidence-based decisions governing sustainable agricultural land management practices require a mechanistic understanding of soil organic matter transformations and stabilization of carbon in soil. Large amounts of carbon from organic fertilizers, root exudates, and crop residues are input into agricultural soils. Microbes then catalyze soil biogeochemical processes including carbon extracellular transformation, mineralization and assimilation of resources that are later returned to the soil as metabolites and necromass. A systems biology approach for a holistic study of the transformation of carbon inputs into stable soil organic matter requires the use of soil ‘omics’ platforms (metagenomics, metatranscriptomics, metaproteomics, and metabolomics). Linking the data derived from these various platforms will enhance our understanding of structure and function of the microbial communities involved in soil carbon cycling and stabilization. In this review we discuss the application, potential and suitability of different ‘omics’ approaches (independently and in combination) for elucidating processes involved in the transformation of stable carbon in soil. We highlight biases associated with these approaches including limitations of the methods, experimental design and soil sampling, as well as those associated with data analysis and interpretation.